Information Resource Management in Economic Systems - Barčkutė, Ona; Skyrius, Rimvydas (Ekonomika, 1997)
In the current decade, information has become a strategic resource in the management of economic entities, and its importance has equalled or surpassed that of traditional resources-capital, labor, and materials. Over time, information technologies (IT) have developed their influence from an automative-type service to a strategic competition and coordination tool. Thanks to IT, coordination patterns in companies and organizations have shifted from traditionally hierarchical to independent horizontal patterns. IT has also changed the information resource management (IRM) function, responding to a need to manage information as a strategic resource.The traditional concept of cost-benefit evaluation in IT applications is being modified into a concept of value against aggregated costs. Value can be defined in several ways, such as strategic match or competitive advantage, but, in any case, value is created in utilizing strategic opportunities and critical success factors. Three components of IRM are defined; technological, managerial, and political. Each of these components possesses its own problems that require more managerial approaches rather than technical ones.